Outcomes of Autologous Stem Cell Transplantation for Non-Hodgkin Lymphoma Patients at a Tertiary Referral Centre - Ajay Prakash; Hugh Goodman (Middle East Journal of Cancer, 2023)
Background: Autologous stem cell transplant (ASCT) has been used as a consolidative treatment modality in non-Hodgkin’s lymphoma (NHL), but its role in NHL management is still evolving. The study aimed to evaluate the patient outcomes based on age, NHL subtypes, and conditioning regimen. Method: We performed a retrospective analysis of NHL patients who received ASCT (n = 140) in our centre from 1992-2015. Data were gathered for this investigation using electronic records and case notes. Refractory illness, relapse, progressive disease, or death were all considered progression events. Time from ASCT to the last follow-up or progression event was used to define progression-free survival (PFS), and time from ASCT to death or the final follow-up was used to define overall survival (OS). Results: Median age at ASCT was 55 years (16-68). Amongst patients ≤60 years (n = 109) and >60 years (n = 31), there was no significant difference in PFS (P = 0.756), OS (P = 0.711), neutrophil (12.5 vs. 11 days) and platelet (12 vs. 14 days) engraftment times. Amongst follicular lymphoma patients (n = 54) who received BEAM (carmustine, etoposide, cytarabine, melphalan) (n = 30) or Cy/TBI (cyclophosphamide/ total body irradiation) (n=24) conditioning, there was no significant difference between PFS (P = 0.111) and OS (P = 0.667). There was no significant difference (P = 0.46) in the incidence of second malignancies in the patient receiving BEAM or TBI-based conditioning. Conclusion: ASCT can be safely performed for NHL in patients >60 years with outcomes similar to those ≤60 years. TBI based conditioning appear safe with similar outcomes to BEAM in follicular lymphoma patients. Prospective studies are needed to confirm these findings.